Incidence of Transalveolar Extraction in Upper First Molar Among Patients Visiting A Dental Hospital - V. J, OVIYA.; MURALIDOSS, HEMAVATHY; GURUNATHAN, DEEPA (The journal of contemporary issues in business and government, 2021)
Transalveolar extraction is a method employed when normal forceps extraction is not possible due to various difficulties which included tooth fracture during normal extractions. Though this technique is employed in clinical practice, it can lead to several complications after surgery. Hence, the objective of this study was to evaluate the incidence of transalveolar extractions of upper first molar. A retrospective study was conducted. Data collection was done through reviewing records of 86000 patients visiting a hospital in Chennai from June(2019) to March(2020). A total of 1453 patients who had undergone extraction of upper first molar were evaluated. Data such as age, gender, type of extraction and tooth number were evaluated. Both frequency and Chi-square tests were done through IBM SPSS statistical analysis. Prevalence of transalveolar extractions in the upper first molar was 1.5% in the study population. Among the individuals who had undergone transalveolar extraction, 59.09% were males and 40.91% were females. About 59.09% of the transalveolar extractions occurred in the age group of 20-40. Within the limits of this study, the incidence of transalveolar extraction was 1.5% of the upper first molar and more prevalent among the 20-40 age group.